Occurrences Salmonella sp. and Escherichia Coli in Bulk and Packaged Chicken Sausages in Surabaya, Indonesia - Deana Fyra Adi Nur; Ratna Yulistiani; Dedin F. Rosida; Dadik Raharjo (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
Salmonella sp. and Escherichia coli are pathogenic bacteria that cause foodborne diseases that often contaminate food and are harmful to human health. Sales of unpackaged (bulk) sausages accompanied by poor hygiene and environmental sanitation conditions have a high potential for Salmonella and Escherichia coli contamination. The purpose of this study was to compare the contamination level of bacterial, Salmonella sp. and Escherichia coli in bulk and packaged chicken sausages as well as to determine the relationship between the hygiene and sanitation of traders and the level of bacterial contamination, Salmonella sp. and Escherichia coli contamination in chicken sausages sold at traditional markets in Surabaya, Indonesia. This research is a cross-sectional study and purposive sampling method. The results showed that the level of bacterial contamination in the bulk chicken sausage was higher (5.98 Log CFU/g) than in packaged chicken sausage (4.83 Log CFU/g). Salmonella sp. contamination in the bulk chicken sausage was higher (44.44%) than in packaged chicken sausage (10.00%) and Escherichia coli contamination in the bulk chicken sausage was higher (22.22%) than in packaged chicken sausage (20.00%). There is a significant relationship between the hygiene and sanitation of traders with the contamination level of bacteria, Salmonella sp., and Escherichia coli in bulk and packaged chicken sausages.